2000
DOI: 10.1126/science.290.5500.2309
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Eukaryotic DNA Replication by Geminin Binding to Cdt1

Abstract: In all eukaryotic organisms, inappropriate firing of replication origins during the G2 phase of the cell cycle is suppressed by cyclin-dependent kinases. Multicellular eukaryotes contain a second putative inhibitor of re-replication called geminin. Geminin is believed to block binding of the mini-chromosome maintenance (MCM) complex to origins of replication, but the mechanism of this inhibition is unclear. Here we show that geminin interacts tightly with Cdt1, a recently identified replication initiation fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
692
2
29

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(752 citation statements)
references
References 19 publications
29
692
2
29
Order By: Relevance
“…These data are in line with our results of repp86 in a large series of 94 patients with MCL (Schrader et al, 2005). Repp86 is a spindle apparatusassociated protein expressed only during S/G2/M, absent in G1 and G0, and thus displaying the same cell cycle expression pattern like geminin (Heidebrecht et al, 1997(Heidebrecht et al, , 2003Lygerou and Nurse, 2000;Wohlschlegel et al, 2000;Madine and Laskey, 2001;Hodgson et al, 2002). We could demonstrate that the majority of the 94 cases have lower repp86 expression than Ki-67, and this indicates a G1 arrest in the subset of cases in our collective.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These data are in line with our results of repp86 in a large series of 94 patients with MCL (Schrader et al, 2005). Repp86 is a spindle apparatusassociated protein expressed only during S/G2/M, absent in G1 and G0, and thus displaying the same cell cycle expression pattern like geminin (Heidebrecht et al, 1997(Heidebrecht et al, , 2003Lygerou and Nurse, 2000;Wohlschlegel et al, 2000;Madine and Laskey, 2001;Hodgson et al, 2002). We could demonstrate that the majority of the 94 cases have lower repp86 expression than Ki-67, and this indicates a G1 arrest in the subset of cases in our collective.…”
Section: Discussionsupporting
confidence: 86%
“…The authors included also Ki-67 and geminin (Lygerou and Nurse, 2000;Wohlschlegel et al, 2000;Madine and Laskey, 2001) in their study and could demonstrate that low-grade lymphomas reside in an 'in-cycle' G1 state and not in G0. In this very important study of Obermann et al (2005), the authors did not analyse the MCM2 expression in relation to clinical data.…”
mentioning
confidence: 99%
“…Importantly, we have demonstrated that dysregulation of these replicative factors occurs in dysplastic states, indicating that it is an early event in tumorigenesis (Williams et al, 1998;Freeman et al, 1999;Stoeber et al, 1999Stoeber et al, , 2002Going et al, 2002). Although Geminin is a potential inhibitor of cell proliferation (McGarry and Kirschner, 1998;Wohlschlegel et al, 2000), a regulator of differentiation (Kroll et al, 1998), and may be required for maintenance of genomic integrity (Saxena and Dutta, 2003), its role in tumour progression remains to be determined.…”
mentioning
confidence: 87%
“…These include elevated CDK activity during the latter half of the proliferative cycle, resulting in activation and/or removal of replication-licensing factors, changes in gene expression and/or cell-cycle-regulated ubiquitin-mediated proteolysis of replication-licensing factors, and expression of a negative regulator of origin licensing known as Geminin during the S, G2 and M phases (Blow and Hodgson, 2002;Nishitani and Lygerou, 2002). Geminin acts as an inhibitor of DNA replication initiation via its interaction with the loading factor Cdt1 and subsequent inhibition of MCM loading onto chromatin (Wohlschlegel et al, 2000;Tada et al, 2001).…”
mentioning
confidence: 99%
“…Inhibition of DNA re-replication involves disassembly of the pre-replication complex (pre-RC), thereby negatively regulating re-firing of already used or useless origins at the end of the S phase (Blow and Dutta, 2005). Redundant mechanisms of regulation include CDK2 and CDK1 inactivating phosphorylations of Cdt1 (Liu et al, 2004;Sugimoto et al, 2004), origin recognition complexes , cdc6 (Petersen et al, 1999) and replication protein A (RPA), and inhibition of Cdt1 by geminin (Wohlschlegel et al, 2000). But, although geminin is thought to be the main negative regulator in higher eukaryotes, CDK1 also plays a central role because conditional inactivation of CDK1 in yeast and human cells induces re-replication (Itzhaki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%